Impact of manganese stress on physiology and quality of pea (Pisum sativum) - KHURANA, NEENA; CHATTERJEE, C; SHARMA, C P (The Indian Journal of Agricultural Sciences, 2013)
An experiment was carried out in winter season of 1995 to study the effect of variable Mn concentration on pea (Pisum sativam L.). ’Azad’ pea was grown in refined sand at 6 levels ranging from acute deficiency (0.0011 mg Mn/ litre) to excess of manganese (11 mg Mn/litre). Apart from characteristic visible symptoms of the nutrient deficiency, the phytomass and seed yield were restricted in low manganese(< 0.55 mg Mn/litre). In leaves, the concentration of chlorophyll (a and b), Hill reaction activity and activities of adenosine triphosphatase and acid phosphatase were reduced and the concentration of nitrite nitrogen and activities of polyphenol oxidase and peroxidase were elevated. In leaves and seeds, the concentratioll of manganese increased with an increase in manganese supply from severe deficiency to excess. In acute manganese deficiency the number of pods was reduced, the seeds were shrivelled and developed necrotic areas. Likewise, it was similar under the conditions of excess manganese. In seeds, the concentration of protein, sugar and starch were decreased substantially and that of phenols increased under manganese stress. In the deficiency (< 0.11 mg Mn/litre) as well as in excess (11 mg Mn/litre) of manganese the activities of acid phosphatase, ex-amylase and invertase were stimulated and that of starch phosphorylase was decreased in mature seeds.